XMM-Newton discovery of X-ray pulsations from RX J0032.9-7348 (= SXP 7.02) - Haberl, F.; Vasilopoulos, G.; Maggi, P.; Maitra, C.; Kaltenbrunner, D.; Rau, A.; Ducci, L.; Kreykenbohm, I.; Weber, P.; Wilms, J.; Udalski, A.; Cheng, H.; et al. (2024)
An X-ray brightening of a source likely associated with the Be X-ray binary candidate RX J0032.9-7348 in the SMC (Kahabka, Pietsch 1996, A & A 312, 919) was recently discovered with the Einstein Probe mission (EP, ATel#16880).
Keywords: Binary; Neutron Star; Pulsar; Star; Transient